Hybrid Cardiovascular Surgery - Osman Tansel Darçın; Ali Ümit Yener; Adnan Yalçınkaya (Genel Tıp Dergisi)
Today, cardiologists and cardiovascular surgeons are more likely to encounter patients with multiple comorbidities and cardiovascular diseases. Percutaneous and surgical techniques alone cannot be successful or are high risk in these patients. By using the strengths of the two methods in a hybrid manner, low-risk procedures can be performed in these patients. With the developing technology, new hybrid procedures can be created for myocardial revascularization, heart valve diseases, aortic and peripheral vascular diseases.